Locally produced organic food: Consumer preferences - Štefan Bojnec; Dacinia Crina Petrescu; Ruxandra Mălina Petrescu-Mag; Carmen Valentina Rădulescu (Amfiteatru Economic Journal, 2019)
Local and organic food production is often linked to geographical identity that drives consumers to buy products due to their intangible attributes such as protection of the environment, support of local communities, and preservation of traditions. The primary objective of this paper was to find out if the Romanian consumers preferred a closer location of organic food production. Research results were based on a random survey, with a sample of 424 people from Romania. Seven variables related to consumer preferences and habits were analyzed through descriptive statistics and by Mann Whitney, Wilcoxon, Kruskal Wallis tests, and Spearman's rank-order correlation coefficient. Three location situations were taken under analysis: local vs. other national locations; national vs. other EU locations; and EU vs. the rest of the world. The results revealed that Romanian consumers were prone to local organic food sources, as long as 65% of them preferred locally produced foods over other national sources. A closer location was also more attractive in the other two tested situations, as follows: 77% of the sample preferred foods from Romania to those from other EU countries and 62% preferred European products to those from the rest of the world. The paper concluded that the promotion of the concept of a closer location could be an unexplored opportunity for those interested in the Romanian market.
Keywords: D12; M31; 330; organic food; local product; consumer preference; Romania